Association of respiratory syncytial virus bronchiolitis with the interleukin 8 gene region in UK families. - Hull, J; Thomson, A; Kwiatkowski, D (2000)
BACKGROUND: Respiratory syncytial virus (RSV) infects nearly all children by the end of their second winter. Why some develop bronchiolitis is poorly understood; it is not known whether there is a genetic component. The pathological features include neutrophil infiltration and high levels of interleukin 8 (IL-8), a potent neutrophil chemoattractant. METHODS: Common genetic variants of the promoter region of the IL-8 gene were identified by sequencing DNA from 36 healthy individuals. Genetic correlates of IL-8 production were assessed using whole blood from 50 healthy subjects. To investigate genetic correlates of disease severity 117 nuclear families were recruited in which a child had required hospital admission for RSV bronchiolitis. RESULTS: A common single nucleotide polymorphism (allele frequency 0.44) was identified 251 bp upstream of the IL-8 transcription start site. The IL8-251A allele tended to be associated with increased IL-8 production by lipopolysaccharide stimulated whole blood (p=0.07). Using the transmission disequilibrium test, the frequency of this allele was significantly increased in infants with bronchiolitis (transmission = 62% (95% confidence interval (CI) 53 to 71), p=0.014) and particularly in those without known risk factors (transmission = 78% (95% CI 62 to 93), p=0.004). CONCLUSION: Disease severity following RSV infection appears to be determined by a genetic factor close to the IL-8 gene. Further analysis of this effect may elucidate causal processes in the pathogenesis of RSV bronchiolitis.